Cumulative inactivation of N-type Ca(V)2.2 calcium channels modified by alternative splicing - Thaler, Christopher (National Academy of Sciences, 2004)
The Ca(V)2 family of voltage-gated calcium channels, present in presynaptic nerve terminals, regulates exocytosis and synaptic transmission. Cumulative inactivation of these channels occurs during trains of action potentials, and this may control short-term dynamics at the synapse. Inactivation during brief, repetitive stimulation is primarily attributed to closed-state inactivation, and several factors modulate the susceptibility of voltage-gated calcium channels to this form of inactivation. We show that alternative splicing of an exon in a cytoplasmic region of the Ca(V)2.2 channel modulates its sensitivity to inactivation during trains of action potential waveforms. The presence of this exon, exon 18a, protects the Ca(V)2.2 channel from entry into closed-state inactivation specifically during short (10 ms to 3 s) and small depolarizations of the membrane potential (–60 mV to –50 mV). The reduced sensitivity to closed-state inactivation within this dynamic range likely underlies the differential responsiveness of Ca(V)2.2 splice isoforms to trains of action potential waveforms. Regulated alternative splicing of Ca(V)2.2 represents a possible mechanism for modulating short-term dynamics of synaptic efficacy in different regions of the nervous system.